ANALISIS EFISIENSI SISTEM PROPORSIONAL TERBUKA PADA PROYEKSI PELAKSANAAN PEMILU SERENTAK 2024 DI INDONESIA - Pramono, Joko; Prianggodo, Chandra Adjie (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2023)
The research explains the open proportional electoral system that leaves many complex experiences and problems in the modern democratic era. The dynamics of national politics over the past decade through the implementation of elections have encouraged the improvement of people's welfare evenly. The purpose of this research is to examine the efficiency of the electoral system with an open proportional concept, supported by relevant theories such as the theory of modern democratic dynamics, the theory of organizing elections, the theory of popularity, the theory of legislative characteristics, and the public perspective. This research method uses a conceptual approach supported by the acquisition of secondary data from various scientific literature or termed library research. Data analysis techniques use the concept of interactive which gives researchers the freedom to process data as effectively as possible without reducing the original meaning. The open proportional system was implemented in the 2019 elections, although the results were ineffective, as evidenced by the findings of many violations by Bawaslu. The open proportional system has advantages and disadvantages for the community, political parties, and election organizing instruments. The open proportional system creates a narrow space for less popular candidates. The proliferation of legislative candidates from among celebrities and artists proves that the open proportional system overrides a person's capabilities. The nature of democracy, which is determined by the majority vote, ultimately creates a strong political climate to appoint popular figures that are loved by the publicPenelitian menjelaskan sistem Pemilu proporsional terbuka yang menyisakan banyak pengalaman dan problematika kompleks Â di era demokrasi modern. Dinamika politik nasional selama satu dekade terakhir melalui pest Pemilu berharap perbaikan kesejahteraan masyarakat secara merata. Tujuan penelitian ini mengkaji efisiensi sistem Pemilu dengan konsep proporsional terbuka yang didukung dengan teori-teori relevan seperti teori dinamika demokrasi modern, teori penyelenggaraan Pemilu, teori popularitas, teori karakteristik legislatif, dan konsep perspektif publik. Metode penelitian ini menggunakan pendekatan konseptual dengan didukung perolehan data sekunder dari berbagai literatur ilmiah atau diistilahkan studi kepustakaan. Teknik analisis data menggunakan konsep interaktif yang memberikan keleluasaan pada peneliti untuk mengolah data seefektif mungkin tanpa mengurangi makna asli. Sistem proporsional terbuka telah dilakukan pada Pemilu 2019, meski hasilnya tidak efektif yang mana dibuktikan dengan temuan banyak pelanggaran oleh Bawaslu. Sistem proporsional terbuka memiliki kelebihan dan kekurangan bagi masyarakat, partai politik, dan instrumen penyelenggara Pemilu. Sistem proporsional terbuka menciptakan ruang sempit bagi kandidat yang kurang populer. Menjamurnya calon legislatif dari kalangan selebriti dan artis membuktikan bahwa sistem proporsional terbuka mengesampingkan kapabilitas seseorang. Sifat demokrasi yang ditentukan suara mayoritas pada akhirnya menciptakan iklim politik kuat untuk mengangkat sosok populer yang digandrungi public.